Development of Mathematic Learning Devices Based on Discovery Learning Model To Facilitate Students’ Mathematic Communication Ability - Uswatun Khasanah; Nahor Murani Hutapea; Zulkarnain Zulkarnain (Journal of Educational Sciences, 2021)
The condition of the learning equipment used by the teacher is not in accordance with the demands of the 2013 curriculum. Learning activities and Student Worksheets (LKPD) used in the learning process have not been able to facilitate the improvement of students' Mathematical Communication Ability (KKM). Teachers have not designed learning tools that can encourage student activities to facilitate the improvement of KKM. This study aims to produce learning tools based on the Discovery Learning model to facilitate the improvement of the KKM of students that are valid and practical. This development research uses the ADDIE development model with the stages of Analysis, Design, Development, Implementation, and Evaluation. The products produced from this research on the development of learning tools are syllabus, lesson plans, LKPD and KKM questions. The results of the validation test for the syllabus, RPP, LKPD and KKM questions obtained consecutively a percentage of 92.19%, 93.37%, 93.14% and 94.64% with very valid categories. The practicality test results got a percentage of 84.52% for small group trials and 94.00% for teacher responses in the very practical category. The results of the validation and practicality test state that mathematics learning tools based on the Discovery Learning model can facilitate students' Mathematical Communication Ability.